Aspects of the ecology of noack’s roundleaf bat (Hipposideros Aff. Ruber) in Ghana - Nkrumah, Evans Ewald (2015)
Thesis submitted to the Graduate School, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for the award of the degree of Doctor of Philosophy (Wildlife and Range Management) 2014